Interpersonal Harmony and Conflict for Chinese People: A Yin–Yang Perspective - Huang, Li-Li (Frontiers in Psychology, 2016)
This article provides an overview on a series of original studies conducted by the author. The aim here is to present the ideas that the author reconstructed, based on the dialectics of harmonization, regarding harmony and conflict embodied in traditional Chinese thought, and to describe how a formal psychological theory/model on interpersonal harmony and conflict was developed based on the Yin-Yang perspective. The paper also details how essential theories on interpersonal harmony and conflict were constructed under this formal model by conducting a qualitative study involving in-depth interviews with 30 adults. Psychological research in Western society has, intriguingly, long been focused more on interpersonal conflict than on interpersonal harmony. By contrast, the author’s work started from the viewpoint of a materialist conception of history and dialectics of harmonization in order to reinterpret traditional Chinese thought. Next, a “dynamic model of interpersonal harmony and conflict” was developed, as a formal psychological theory, based on the real-virtual notions in the Yin-Yang perspective. Under this model, interpersonal harmony and conflict can be classified into genuine versus superficial harmony and authentic versus virtual focus conflict, and implicit/hidden conflict is regarded as superficial harmony. Subsequently, the author conducted a series of quantitative studies on interpersonal harmony and conflict within parent-child, supervisor-subordinate, and friend-friend relationships in order to verify the construct validity and the predictive validity of the dynamic model of interpersonal harmony and conflict. The claim presented herein is that Chinese traditional thought and the psychological theory/model based on the Yin-Yang perspective can be combined. Accordingly, by combining qualitative and quantitative empirical research, the relative substantial theory can be developed and the concepts can be validated. Thus, this work represents the realization of a series of modern Chinese indigenous psychological research studies rooted in traditional cultural thought and the Yin-Yang perspective. The work also mirrors the current conflict-management research that has incorporated the Chinese notion of harmony and adopted the Yin-Yang perspective on culture.